KRASNOYARSK REGIONAL MORBID ANATOMY BUREAU - N. M. Koretskaya; E. N Grin; L. A. Babenko; S. S. Bekuzarov (Туберкулез и болезни лёгких, 2016)
The article presents the clinical case of thyroid tuberculosis, diagnosed during thyroidectomy in the female patient suffering from nodular toxic goiter. Doctors are to be made aware about the rare localization of tuberculosis for its timely detection.